A randomised trial deploying a simulation to investigate the impact of hospital discharge letters on patient care in general practice. Issue 7 (8th July 2014) - Jiwa, Moyez; Meng, Xingqiong; O'Shea, Carolyn; Magin, Parker; Dadich, Ann; Pillai, Vinita
Abstract : Objective: To determine how the timing and length of hospital discharge letters impact on the number of ongoing patient problems identified by general practitioners (GPs). Trial design: GPs were randomised into four groups. Each viewed a video monologue of an actor-patient as he might present to his GP following a hospital admission with 10 problems. GPs were provided with a medical record as well as a long or short discharge letter, which was available when the video was viewed or 1 week later. GPs indicated if they would prescribe, refer or order tests for the patient's problems. Methods: Setting Primary care. Participants Practising Australian GPs. Intervention A short or long hospital discharge letter enumerating patient problems. Outcome measure Number of ongoing patient problems out of 10 identified for management by the GPs. Randomisation 1:1 randomisation. Blinding (masking) Single-blind. Results: Numbers randomised 59 GPs. Recruitment GPs were recruited from a network of 102 GPs across Australia. Numbers analysed 59 GPs. Outcome GPs who received the long letter immediately were more satisfied with this information (p<0.001). Those who received the letter immediately identified significantly more health problems (p=0.001). GPs who received a short, delayed discharge letter were less satisfied than those who received a longer delayed letter (p=0.03); however, both groups who received the delayed letter identified a similar number of health problems. GPs who were older, who practised in an inner regional area or who offered more patient sessions per week identified fewer health problems (p values <0.01, <0.05 and <0.05, respectively). Harms Nil. Conclusions: Receiving information during patient consultation, as well as GP characteristics, influences the number of patient problems addressed. Trial registration number: ACTRN12614000403639.